An efficient GPU out-of-core framework for interactive rendering of large-scale CAD models - Xue, Junjie; Zhao, Gang; Xiao, Wenlei (Computer animation and virtual worlds, 2016)
Real‐time rendering of large‐scale engineering computer‐aided design (CAD) models has been recognized as a challenging task. Because of the constraints of limited graphics processing unit (GPU) memory size and computation capacity, a massive model with hundreds of millions of triangles cannot be loaded and rendered in real‐time using most of modern GPUs. In this paper, an efficient GPU out‐of‐core framework is proposed for interactively visualizing large‐scale CAD models. To improve efficiency of data fetching from CPU host memory to GPU device memory, a parallel offline geometry compression scheme is introduced to minimize the storage cost of each primitive by compressing the levels of detail (LOD) geometries into a highly compact format. At the rendering stage, occlusion culling and LOD processing algorithms are integrated and implemented with an efficient GPU‐based approach to determine a minimal scale of primitives to be transferred for each frame. A prototype software system is developed to preprocess and render massive CAD models with the proposed framework. Experimental results show that users can walkthrough massive CAD models with hundreds of millions of triangles at high frame rates using our framework. Copyright © 2016 John Wiley & Sons, Ltd. This paper proposes an efficient graphics processing unit out‐of‐core framework for interactively visualizing large‐scale computer‐aided design models. An off‐line geometry compression scheme is introduced to minimize the storage cost of each primitive. Occlusion culling and level of detail processing algorithms are integrated with an efficient graphics processing unit‐based approach to determine a minimal scale of primitives to be transferred for each frame. The effectiveness and robustness of the framework are verified by testing on several computer‐aided design models with hundreds of millions of triangles at high frame rates.